Storage stability of freeze-dried arazá (Eugenia stipitata Mc Vaugh) powders. Implications of carrier type and glass transition - Reyes Alvarez, Camilo Andres (2020)
Arazá, a flavorsome fruit rich in antioxidants (phenolics/carotenoids/flavonoids/ascorbic acid) may be appropriate for preparing powdered-functional foods and beverages. Variations in water-activity (aw) and matrix physical state (glassy/rubbery) can induce undesirable changes in dehydrated products color antioxidant composition/activity reducing shelf-life. Solving this problem requires a thorough analysis of the aw/physical state effects on the arazá powder physicochemical properties. Objectives were to: (a) analyse aw, glass-transition temperature (Tg) and carrier-type (maltodextrin-DE10/Arabic-gum) effects on freeze-dried arazá color, antioxidant composition/activity; (b) Determine storage-time influence on antioxidant content/activity/polyphenol composition considering the best performing aw values previously determined. Critical aw values calculated from Tg/aw interrelationship overestimated the aw limit corresponding to samples color/antioxidant composition/activity maximum stability, therefore, Tg was not a reliable indicator of the properties stabilities. Antioxidant content/activity storage behavior (20 °C/aw = 0.11 (best performing aw optimized across all properties)) were satisfactorily predicted by the Weibull equation. Shelf-lives, calculated considering 90% properties retention as the acceptability limit, were 34 (arazá/maltodextrin) and 50 (arazá/Arabic-gum) days. Polyphenolic profile included 6 phenolic acids, one coumaric acid derivative, 4 flavonoids and one ellagitannin. Using a mix of maltodextrin-DE10/Arabic-gum might improve antioxidant content/activity stability obtained with the single carriers and extend their shelf-life.